PEMBUATAN PRODUK MINUMAN FUNGSIONAL DARI BUNGA TELANG DI DESA SUKOMORO KABUPATEN MAGETAN - Agustina, Nia; Barqin, Gesa Aldin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community engagement program aimed to enhance the capacity of residents in Sukomoro Village, Magetan, to utilize butterfly pea (Clitoria ternatea L.) as a functional beverage product with both health and economic value. The program addressed limited community knowledge on proper processing techniques, food sanitation, and product development. Participatory counseling, hands-on training, demonstrations, and pretest–posttest evaluations were implemented to strengthen participants' competencies. Training included the functional properties of butterfly pea, processing methods, and packaging and labeling principles. The results showed a significant improvement in knowledge, indicated by an increase in the average score from 71 to 85. Participants were also able to independently produce several functional products, including butterfly pea tea, milk, and jelly. Overall, the program successfully empowered the community and supported the development of micro-enterprises based on local resources.